(untitled) (Scientific journal of the Fergana State University, 2025)
This article talks about reforms implemented in the field of internal affairs during the years of independence, measures aimed at strengthening the legal basis of organizing the activities of police officers. The article also deeply analyzes social life in the republic and its impact on public safety. In particular, social protests, violations, minor and major crimes caused by economic problems among the population in the first years of independence were analyzed with exact figures. In order to eliminate these situations in the Republic, the article describes the issues of social protection of the population and thereby the mechanisms of reducing crime. \